Synthesis and Photocatalytic Property of b-In2S3 Nanocrystals - Liu, Guodong (Asian Journal of Chemistry, 2011)
Tetragonal b-In2S3 nanocrystals have been successfully synthesized via a simple solvothermal route. The b-In2S3 nanorods show good photocatalytic properties under sunlight irradiation.